Inferior vena cava filter: Is it a way out of pulmonary embolism in gynaecological cancer? - Case report - Shafiee MN,; Ani Amelia Z,; Rozman Z,; Nur Azurah AG, (Department of Surgery, UKM Medical Centre, 2011)
Venous thromboembolism has a strong association with pelvic malignancy, whereby a failure in recognizing this event will lead to mortality. The best intervention depends on the individual basis with the availability of supporting service. We illustrate a case of gynaecological malignancy with concurrent deep vein thrombosis undergoing staging laparotomy and debulking surgery. Inferior vena cava filter was inserted after initial thrombolytic therapy and subsequently a long term treatment. Death from massive pulmonary embolism and major bleeding was prevented and synchronous primary ovarian and endometrial cancer prognosis was reassured in this case.